Scaling networks v6 companion guide (Cisco Press, 2018)
"Scaling Networks v6 Companion Guide is the official supplemental textbook for the Scaling Networks v6 course in the Cisco Networking Academy CCNA Routing and Switching curriculum. The Companion Guide is designed as a portable desk reference to use anytime, anywhere to reinforce the material from the course and organize your time. The book's features help you focus on important concepts to succeed in this course."--Provided by publisher